Analysis of Students' Chemistry Anxiety: A Systematic Literature Review - Annida Hanifah Maulida; Jaslin Ikhsan (Jurnal Pendidikan Kimia Indonesia, 2025)
Anxiety is one of the emotional disorders commonly experienced by students and can affect learning outcomes. This study used a systematic literature review (SLR) method to identify level of education, measurement instruments, and contributing factors to chemistry anxiety. Data were collected from the Scopus database using Publish or Perish (PoP), ProQuest, and Eric. This study reviewed 27 articles that met the inclusion criteria. The analysis showed that most studies (59.3%) were conducted at the collage level. The most widely used chemistry anxiety instrument is the Chemistry Laboratory Anxiety Scale. The dominant factors that cause chemistry anxiety include fear of failure and making mistakes, chemistry that is considered difficult and negative feelings or perceptions towards chemistry. These findings provide important implications for teachers to design learning strategies that can minimize anxiety and support students' emotional well-being in chemistry.